2015
DOI: 10.1186/s40066-015-0021-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring gender perceptions of resource ownership and their implications for food security among rural livestock owners in Tanzania, Ethiopia, and Nicaragua

Abstract: Background: Productive resources are essential to the livelihoods and food security of the world's rural poor. Gender-equal ownership of resources is considered key to increasing agricultural productivity, equity, and food security. However, there has not been much research about local understandings of ownership particularly in the Global South. In addition, research is also lacking about how concepts of ownership affect food security at the household level.Results: This paper discusses the variability of loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 22 publications
3
67
0
Order By: Relevance
“…In her study across Indonesia, Bolivia, Peru and Kenya, Valdivia (2001), shows that women's control over livestock, livestock products and the productive resources needed to raise livestock, increases women's bargaining power, access to animal source foods that they use mostly to benefit their children and ultimately their empowerment. A study in Tanzania, Ethiopia, and Nicaragua showed how the informal nature of livestock ownership affected perceptions of "what it means to own livestock," with women and men respondents using various criteria such as "who contributes most labor in the management of the livestock", "who sourced it" or "who controls the revenues" (Galiè et al 2015). The WELI thus, does not include questions on "livestock ownership" but focuses on access to and control over livestock or its management.…”
Section: Dimensions Of Empowerment In the Welimentioning
confidence: 99%
See 1 more Smart Citation
“…In her study across Indonesia, Bolivia, Peru and Kenya, Valdivia (2001), shows that women's control over livestock, livestock products and the productive resources needed to raise livestock, increases women's bargaining power, access to animal source foods that they use mostly to benefit their children and ultimately their empowerment. A study in Tanzania, Ethiopia, and Nicaragua showed how the informal nature of livestock ownership affected perceptions of "what it means to own livestock," with women and men respondents using various criteria such as "who contributes most labor in the management of the livestock", "who sourced it" or "who controls the revenues" (Galiè et al 2015). The WELI thus, does not include questions on "livestock ownership" but focuses on access to and control over livestock or its management.…”
Section: Dimensions Of Empowerment In the Welimentioning
confidence: 99%
“…Livestock also offers a unique opportunity for the empowerment of rural women, who are more likely to access and control livestock and their products than other productive resources such as land and machinery (Galiè et al 2015;Njuki and Sanginga 2013). Thereby, livestock also is an important means of enhancing gender equity in livestock systems and contributing to gender equality.…”
Section: Introductionmentioning
confidence: 99%
“…In such situations gender disparity could raise, with women losing important assets. A different question formulation could be investigated in this respect in further studies, to obtain more accurate information and assess capacity of women to respond to 'household internal shocks' [43].…”
Section: Socioeconomic Characterisationmentioning
confidence: 99%
“…There is relatively little research in Ethiopia on gender and the related socioeconomic factors that may constrain sweetpotato production (Aguilar et al, 2014). Most research on gender opportunities and constraints in agriculture focuses on crops like wheat and on livestock rearing (Mogue et al, 2009;Galiè et al, 2015). But some of that work and experiments may have application in gender and sweetpotato production.…”
Section: Objectives and Scope Of The Study And Its Position In The Qdmentioning
confidence: 99%